2019
DOI: 10.1111/desc.12901
|View full text |Cite
|
Sign up to set email alerts
|

What do bilingual infants actually hear? Evaluating measures of language input to bilingual‐learning 10‐month‐olds

Abstract: Examining how bilingual infants experience their dual language input is important for understanding bilingual language acquisition. To assess these language experiences, researchers typically conduct language interviews with caregivers. However, little is known about the reliability of these parent reports in describing how bilingual children actually experience dual language input. Here, we explored the quantitative nature of dual language input to bilingual infants. Furthermore, we described some of the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 47 publications
(69 reference statements)
3
43
0
Order By: Relevance
“…Another limitation is that these estimates were based on parent reports of relative exposure. While reported measures of relative language exposure are widely used in the literature for reasons of convenience (Byers-Heinlein et al, 2019;De Anda, Bosch, et al, 2016;Marchman & Martínez-Sussmann, 2002;Orena et al, 2019), they do not capture individual variation in the absolute amount of language that children experience which are likely to have significant impacts on outcomes (Marchman et al, 2017;Orena et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…Another limitation is that these estimates were based on parent reports of relative exposure. While reported measures of relative language exposure are widely used in the literature for reasons of convenience (Byers-Heinlein et al, 2019;De Anda, Bosch, et al, 2016;Marchman & Martínez-Sussmann, 2002;Orena et al, 2019), they do not capture individual variation in the absolute amount of language that children experience which are likely to have significant impacts on outcomes (Marchman et al, 2017;Orena et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…This study did not report participants' bilingual language dominance, but all speakers identified as Quechua-Spanish bilinguals and reported using both languages. However, bilingual children, including those in the current study, are rarely exposed to or use equal quantities of their two languages (Orena et al 2020). Naturalistic assessments of the child Quechua-Spanish speakers' bilingual language practices has been reported elsewhere (Cychosz 2020a); results showed that there is variability in the amount of Spanish and Quechua that the children use.…”
Section: Effects Of Bilingual Statusmentioning
confidence: 61%
“…Another Combined with smart sampling and annotation procedures, they offer new insight into children's everyday environments. Nevertheless, the environmental factors were computed from a single daylong recording which does not capture the complexities of a child's learning experience Orena, Byers-Heinlein, and Polka (2020). For example, when the child participants from this study travel to more rural areas, where more monolingual Quechua speakers live, the children are more likely to speak Quechua.…”
Section: Environmental Effects On Coarticulation By Word Environmentmentioning
confidence: 99%